The Effect of Sun Exposure on the Effectiveness of the Serotonin Hormone: Literature Review - Mutiara Sari; Elsa Yuniarti (Jurnal Biologi Tropis, 2023)
Indonesia is a tropical country on the equator and is always in the sun all day long. The sun is an aspect that has a significant impact on human health. The purpose of conducting this literature review is to provide information to readers regarding the effect of sun exposure on levels of the hormone serotonin. The method used in this writing is a literature review article (LRA) with library sources obtained through the Publish Or Perish data base which was published from 2010 to 2022 with the topic Effects of Sun Exposure on Serotonin Levels. This literature review uses keywords including exposure, sun, vitamin D, hormones, and serotonin. The journal results from the search obtained 67 journals which included inclusion, namely 57 journals then were selected with topic relevance, there were only 10 journals. Based on the results of the literature review of the article, it was found that sunlight affects human health, one of which is stimulating the formation of the hormones serotonin and Vitamin D.